PENGARUH RETURN ON EQUITY, DEBT TO ASSET RATIO DAN CASH RATIO TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Cindy Agustin Hermalia Putri; Puji Astuti; Sugeng Sugeng (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
The industrial sector's manufacturing businesses, especially those in the property and real estate subsector, significantly contribute to the growth of the national economy. Firm value becomes an important metric for investors to evaluate a company's performance and prospects in the face of global economic challenges and fierce market competition. Leverage, liquidity, and profitability are just a few of the internal basic elements that can affect a company's value. The purpose of this study is to examine how the cash ratio, debt to asset ratio, and return on equity affect the firm value of manufacturing companies in the industrial sector that are listed on the Indonesia Stock Exchange for the 2022–2024 period. This study uses the ex post facto method in a quantitative manner. Purposive sampling was used to pick a sample of 18 enterprises, yielding 54 observational data points over a three-year period. Multiple linear regression analysis was used to examine the data, which came from the companies' annual financial reports. The findings show that while DAR has no discernible impact on company value, ROE and cash ratio do, to a certain extent. At the same time, cash ratio, DAR, and ROE all have a big impact on company value. This study can be taken into account by investors and management, showing that while leverage should be properly managed, a company's profitability and liquidity performance are more important in raising the market's view of firm worth.